The penal system of colonial Natal : from British roots to racially defined punishment - Pete, Steve (Institute of Criminology, 2016)
This thesis does not claim to be a complete penal history of the colony of Natal. Rather it investigates selected themes which characterized Natal's penal system during the period 1842 to 1910. It attempts thus to reveal both the similarity of that system to the penal systems of the advanced capitalist states as well as its essentially unique character. The continuities between penal practice in Natal and elsewhere in the capitalist world do not seem difficult to explain; Natal was after all a colonial possession of the world's oldest and most advanced capitalist state. With the annexation of Natal to the British Empire in 1842, and the introduction of the British administration in 1845, the colony became part of a single expanding world capitalist economy. The legal and administrative institutions which were set up to govern and regulate this new market in the interests of the Empire, were, modelled upon British institutions. These institutions had developed with, and formed an integral part of the system of industrial capitalism. The officials and administrators sent out from "home" to operate these new institutions were likewise ideological products of the most industrialised and developed capitalist country in the world. Thus the penal system imported into Natal in the middle of the nineteenth century, and all the ideological baggage which came with that system, had its roots in the metropolitan country, where the punishment of imprisonment had arisen with the development of capitalism, and was linked thereto. Any study of the penal system of Natal thus cannot ignore the origins of imprisonment as a form of punishment, and the reasons for its development along with the rise of capitalism in Europe. It would be a mistake, however, simply to point to the similarity of the prisons of Natal to prisons in the mother country. While Natal's economy was certainly integrated, as a peripheral sector, with a single world capitalist economy, it could certainly not be described as capitalist in nature. The prison in Europe had emerged as a response to large scale industrialisation and the rapid expansion of capitalist relations of production. Until the last decades of the nineteenth century, Natal had no industries worth speaking of. In addition the white colonists were confronted by a large indigenous population, which fiercely and successfully resisted being drawn into wage labour for the white man, which in effect meant subjection to capitalist relations of production. Natal's penal system must thus be seen in the context of the colonial situation. To a large extent the role of the prison in Natal and the ideologies of punishment which developed in the colony over the years, were a response to specific local conditions. It is this fact that makes the penal system of Natal unique. This thesis is thus concerned with both continuity and originality; the articulation of the penal theories and assumptions of an industrialised metropolitan political economy, with a rural colonial political economy.